2019
DOI: 10.6061/clinics/2019/e829
|View full text |Cite
|
Sign up to set email alerts
|

Swimming training potentiates the recovery of femoral neck strength in young diabetic rats under insulin therapy

Abstract: OBJECTIVE: To test whether swimming training benefits femoral neck strength in young diabetic rats under insulin therapy. METHODS: A total of 60 male Wistar rats (age: 40 days) were divided equally into the following six groups: control sedentary, control exercise, diabetic sedentary, diabetic exercise, diabetic sedentary plus insulin and diabetic exercise plus insulin. Diabetes was induced with a unique intraperitoneal injection (60 mg/kg body weight) of streptozotocin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The applied treatment with insulin enhanced the femoral midshaft tenacity in diabetic rats. As bone tenacity is determined primarily by the unmineralized matrix [ 26 ], it is conceivable that the observed insulin benefit to femoral tenacity is due to an increase in the femoral collagen content promoted by insulin in this model of experimental diabetes, as reported previously by our group [ 10 ].…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…The applied treatment with insulin enhanced the femoral midshaft tenacity in diabetic rats. As bone tenacity is determined primarily by the unmineralized matrix [ 26 ], it is conceivable that the observed insulin benefit to femoral tenacity is due to an increase in the femoral collagen content promoted by insulin in this model of experimental diabetes, as reported previously by our group [ 10 ].…”
Section: Discussionmentioning
confidence: 64%
“…Thus, it is conceivable that the diminished femoral area, BMC, BMD and cortical thickness resulted in reduced bone resistance to fracture in the diabetic rats. Although it was not measured in the present study, reduced collagen content has been reported in this model of severe diabetes [ 10 ]. Concerning the low tenacity observed in diabetic rats, it is possible that a reduction in the femoral collagen in these rats has contributed to such damage, since this measure relies on the unmineralized matrix [ 26 ].…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations